2020
DOI: 10.37729/scripta.v7i2.830
|View full text |Cite
|
Sign up to set email alerts
|

Model of School Management Based on Islamic Education

Abstract: This research is revieweing the school management based on islamic education. It aims to obtain an overview of the implementation of Islamic boarding school education and a model for the development of education management at the Darul Hikmah Kutoarjo Islamic boarding school. This research problem will focus on how to plan, organize, coordinate, and control Islamic boarding schools. To answer the research problem, this type of qualitative research is used with a descriptive-analysis approach. The results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Educational institutions such as Madrasah Aliyah Amsilati stand as a place of learning and as a centre for character-building and spiritual students. In this madrassa, the leadership of the head of the madrasah is crucial because they not only manage the administrative and academic aspects but are also responsible for integrating Islamic values into all aspects of education, including extracurricular activities (Saputra et al, 2020;Ayuningsih et al, 2020;Diana, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Educational institutions such as Madrasah Aliyah Amsilati stand as a place of learning and as a centre for character-building and spiritual students. In this madrassa, the leadership of the head of the madrasah is crucial because they not only manage the administrative and academic aspects but are also responsible for integrating Islamic values into all aspects of education, including extracurricular activities (Saputra et al, 2020;Ayuningsih et al, 2020;Diana, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Today's world education standards have changed due to the increasing literacy rate which is associated with the wide adoption of education in the process of developing the character of students in the Industrial Revolution 4.0 era (Agih, 2015). Additionally, the rapid advancement in technology, education, and other sectors has been found to influence certain factors such as the supply chain needed to integrate a proper education system in order to address global issues (Farah, 2013;Nuryana, 2019;Saputra et al, 2020;Almutawa, 2020;Brooks & Mutohar, 2018;Susanti, 2018;Agih, 2015;Al-Huneidi & Schreurs, 2012;Thai et al, 2017;Ramadhani, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it could also be seen through the large number of conglomerate communities or the upper middle class who put their children to Islamic educational institutions, ranging from early education to higher education. This showed that Islamic educational institutions had started to rise and were able to face the flow of globalization with the spirit of working hard and tirelessly (Saputra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%